Answer:
x= -6, y= 10
Step-by-step explanation:
x= y + 4
2x = 3y - 2
If we replace "x" with "y+4" in the second equation we get:
2(y+4) = 3y - 2
2y + 8 = 3y - 2
2y - 3y = -2-8
-y = -10
y = 10
Now we can go back to the first equation and solve for x:
x = y + 4
x = 10 + 4 = 14
You can factor (x^3 and 6x^2) and (-4x and -24).
So x^2(x+6) - 4(x+6)
(x^2-4)(x+6)
(x-2)(x+2)(x+6)
Answer:
1,000,000
Step-by-step explanation:
10^3*10^3
Answer:

Step-by-step explanation:
Its given:

Answer:
m√n + 2n -n√m
Step-by-step explanation:
Solution:
4√n^2 +√m^2n - √4n^2 - √mn^2
= 4n + m√n - 2n - n√m
= m√n + 4n - 2n - n√m
Therefore, m√n + 2n -n√m
PLZ MARK ME AS BRAINLIEST!!!